WIKIPEDIA PROJECT TO TEACH ACADEMIC WRITING IN AN EAP UNIVERSITY COURSE - Horgan, Joseph Jack (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The introduction of modern information and communication technologies (ICT) into the classroom has led to a number of challenges and opportunities for instructors across the field of education. Wikipedia, a collaborative encyclopedia, has proven to be one of the most controversial online platforms throughout academia, with many higher education instructors banning its use outright. Despite the prevailing negative attitude, there has been a recent shift in thought among some in the field regarding its utilization as a teaching tool in a number of applications. One popular use is as the centre of a writing project, most commonly the creation of a new article or the improvement of a pre-existing one.This paper outlines a case study conducted at the Latvia University of Life Sciences and Technologies in the autumn semester of 2019, in which first year international veterinarian medicine students wrote Wikipedia articles as part of a semester-long project in an English for academic purposes course in order to improve academic writing skills such as researching, analysing, summarizing, and editing. Analysis of two questionnaires and the students’ work suggest that despite some challenges, a Wikipedia article writing project can serve as an engaging, rewarding, and effective method to teach academic writing skills.